PEMAHAMAN MASYARAKAT TERHADAP KEWAJIBAN ZAKAT DI KECAMATAN ILIR BARAT II KOTA PALEMBANG - Citra Pertiwi (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2021)
This journal examines the extent to which efforts must be made so that an understanding of zakat obligations builds awareness for zakat in Ilir Barat II sub-district, in this study a case study is carried out on the things that are the factors of opportunities and obstacles to the implementation of zakat with good, transparent, and accountable management. , examines the techniques and strategies that must be done to achieve good management. In the implementation of zakat, there is a gap that is very suitable for the Muslim community to carry out the pilgrimage, which is greater than with the implementation of other pillars of Islam, for example, zakat. This is influenced by internal and external factors of the Muslims themselves, including, the knowledge and understanding of the not yet comprehensive tithe and the lack of application of zakat ritual values ​​in social life. In this study, the type of